Implementation of Village Land Utilization Policy in Bantul Regency - Farida Khasanah, Nor; Laksamana, Rofiq; Rahmanto, Nur; Nashih Luthfi, Ahmad; Salim, M. Nazir (Marcapada: Jurnal Kebijakan Pertanahan, 2023)
The Special Region of Yogyakarta has experienced developments (or can also be termed as "regressions") in the enforcement of land regulation since time immemorial. A new chapter commenced following the enactment of Law No. 13 of 2012 on the Special Status of the Yogyakarta Special Region (UUK). One of the provisions in Article 7, Paragraph (2) of UUK pertains to land affairs, which, among other things, led to the issuance of the Yogyakarta Special Region Governor Regulation (Pergub) No. 34 of 2017 on Village Land Utilization. This research aims to identify the issues arising from the implementation of Pergub No. 34 of 2017 within the various institutions vested with authority in the implementation of this policy. A qualitative methodology was employed in this study, utilizing observation, interviews, and an intensive document analysis approach. Villages serve as the governing bodies directly responsible for Village-owned Land and are mandated to conduct an identification of Sultan/Pakualaman Ground for the purpose of changing its status to the ownership of the Sultan/Pakualaman. The Department of Land and Spatial Planning, acting as the facilitator for the planning and implementation of land affairs and spatial planning, subsequently carries out inventory, identification, and verification processes. Furthermore, it oversees the utilization of Village Land with the Right of Anggaduh. The implementation of Pergub No. 34 of 2017 on Village Land Utilization has been carried out by all relevant departments or stakeholders possessing authority and/or serving as facilitators on behalf of the Sultanate of Ngayogyakarta/Dutchy of Pakualaman.